Autonomous Configuration Method for Real-Time Location Systems - Edelhäußer, Thorsten; Kókai, Gabriella (Proceedings NASA/ESA Conference on Adaptive Hardware and Systems (AHS 2009), 2009)
We introduce a new method for estimating the position and direction of receiving elements of a Real-Time Location System (RTLS). We deployed an autonomous robot and an Evolutionary Algorithm (EA) for this problem. The adopted operations and fitness calculation of the EA are presented for an Angle of Arrival (AoA) system and the results of simulation and real experiment setup were shown. Further problems of implementing in a real scenario were discussed.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD2.autono
Keywords: Angle of Arrival; Autonomous configuration; Evolutionary Algorithm; RTLS